2007
DOI: 10.1111/j.0030-1299.2007.15391.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of large‐scale disturbance on metacommunity structure of terrestrial gastropods: temporal trends in nestedness

Abstract: Distributions of species often exhibit nested structure, such that assemblages at species-poor sites are proper subsets of taxa at more species-rich sites. Traditionally, this has been viewed as a large-scale biogeographic pattern and treated implicitly as static from a temporal perspective. Nonetheless, recent work suggests that nestedness may arise at multiple spatio-temporal scales. A 13-year data set encompassing the effects of two largescale natural disturbances (hurricanes Hugo and Georges) on terrestria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 87 publications
1
89
0
2
Order By: Relevance
“…As our analytical tool is relatively novel, we were not able to assess whether this pattern is characteristic for gastropod communities in general, or only for gastropod communities in alpine grasslands. Other studies showed that differences in habitat quality explain nestedness in litter-dwelling land snail communities in boreal riparian forest (Hylander et al 2005) and that large-scale disturbances by hurricans altered the degree of nestedness in land snail communities in tropical wet forest in Puerto Rico (Bloch et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…As our analytical tool is relatively novel, we were not able to assess whether this pattern is characteristic for gastropod communities in general, or only for gastropod communities in alpine grasslands. Other studies showed that differences in habitat quality explain nestedness in litter-dwelling land snail communities in boreal riparian forest (Hylander et al 2005) and that large-scale disturbances by hurricans altered the degree of nestedness in land snail communities in tropical wet forest in Puerto Rico (Bloch et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In both marine and terrestrial systems, it is becoming clear that understanding resilience to disturbance requires investigation of dispersal in addition to local influences, as demonstrated by field studies in estuaries (Thrush et al, 2008), forests (Bloch et al, 2007), and streams (Campbell et al, 2015).…”
Section: Integrating Metacommunity Theory and Field Observationsmentioning
confidence: 99%
“…3). From measurements after Hurricanes Hugo and Georges, Bloch et al (2007) determined that the patchiness of canopy structure produced by hurricanes is particularly important for predicting sites occupied by snails. In general, it was surprising to find that the canopy trimming (including Trim + debris plots) had such a large effect on decreasing populations of litter arthropods (Richardson et al, 2010), gastropods , and coqui frogs (Klawinski et al, 2014), whereas debris addition had (in most cases) little to no effect on these populations.…”
Section: Population and Community Attributesmentioning
confidence: 99%
“…Predator-prey relationships need further examination following hurricane passages to better determine drivers of changes and cascading trophic effects (e.g., Richardson et al, 2010;Schowalter et al, 2014). Movement dynamics appear critical to better understand both the importance of patch size effects on animal populations (e.g., Bloch et al, 2007) and the extent to which predators (e.g., coqui frogs, some arthropods) track prey after hurricanes. Diet shifts in predators may also be expected with the hypothesized changes in available habitat and prey that result from hurricanes (Waide, 1991).…”
Section: Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation